An Analysis Of Mini Control Timer System For PDAM Water Processing Using Wave Control Method - Rudi Saputra; Yopi Andinata; Beni Satria (Jurnal Scientia, 2024)
In this study, a mini control timer system was analyzed in PDAM water treatment using the Control Wave method. In a water treatment system, timely control is very important to ensure optimal operational efficiency and water quality. The Control Wave method is applied to regulate and optimize the water treatment process more efficiently through automatic timer-based control. This system allows more flexible adjustments to variations in workload and operational conditions, thereby improving the overall performance of the water treatment process. which involves the development of a simulation model that describes the water treatment process with the integration of a Control Wave-based control system. The simulation results show that this method can improve energy efficiency, reduce downtime, and increase the stability of water treatment operations. In addition, the implementation of Control Wave in this mini control timer system has also been proven to be able to adjust to changes in operational needs dynamically, without sacrificing the quality of the processed water. The findings of this study provide a basis for further improvements in the control system in PDAM water treatment, especially in the use of automation technology to improve process reliability and efficiency.